Characteristics of private partners in Chiranjeevi Yojana, a public-private-partnership to promote institutional births in Gujarat, India – Lessons for universal health coverage - Iyer, Veena (PLoS One, 2017)
BACKGROUND: The Chiranjeevi Yojana (CY) is a Public-Private-Partnership between the state and private obstetricians in Gujarat, India, since 2007. The state pays for institutional births of the most vulnerable households (below-poverty-line and tribal) in private hospitals. An innovative remuneration package has been designed to disincentivise unnecessary cesareans. This study examines characteristics of private facilities which participated in the program. METHODS: We conducted a cross-sectional survey of all facilities which had conducted any births between June 2012 and April 2013 in three districts. We identified 111 private and 47 public facilities. Ninety of the 111 private facilities did caesarean sections in the last three months and were eligible to participate in the CY program. Of these, 40 (44%) participated in the CY program. We conducted descriptive and bivariate analyses followed by a Poisson regression model to estimate prevalence ratios of facility characteristics that predicted participation. RESULTS: We found that facilities participating in the CY program had a significantly higher likelihood of being general facilities (PR 1.9, 95% CI 1.3–2.9), or conducting lower proportion of cesarean births (PR 2.1, 95% CI 1.2–3.5) or having obstetricians new in private practice (PR 1.9, 95% CI 1.2–3.1) or being less expensive (PR 1.8, 95% CI 1.1–3.0). But none of these factors retained significance in a multi variable model. CONCLUSION: Private obstetricians who participate in the CY program tend to be new to private practice, provide general services, conduct fewer caesareans and are also less expensive. This is advantageous to the PPP and widens the target beneficiary groups that can be serviced by the PPP. The state should design remuneration packages with the aim of attracting relatively new obstetricians to set up practices in more remote areas. It is possible that the CY remuneration package design is effective in keeping caesarean rates in check, and needs to be studied further.